The Role of Technology Integration in ASEAN Young Entrepreneurs Collaboration: Opportunities and Challenges in the Ecosystem - Sofiana, Dina; Soegoto, Dedi Sulistiyo; Yunanto , Rio (Universitas Komputer Indonesia, 2025)
The development of digital technology has changed the business landscape in ASEAN, enabling young entrepreneurs to collaborate across countries. This study analyzes the role of technology integration in driving business collaboration and opportunities and challenges in the digital ecosystem. A qualitative approach based on literature studies and case analysis is used to explore the role of digital platforms such as startup hubs, fintech, and marketplaces in expanding market access and innovation. The results show that technology integration supports the growth of young entrepreneurs' businesses through platforms such as Gojek, Tokopedia, and AirAsia Super App. There are still challenges, such as digital infrastructure gaps, regulatory differences, and cultural factors, which are still obstacles to cross-country collaboration. This study recommends harmonizing ASEAN digital policies, improving technology infrastructure, and developing digital-based education and mentoring programs to strengthen the young entrepreneurial ecosystem in ASEAN.